2007
DOI: 10.1016/j.biopsych.2006.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis and Helplessness Are Mediated by Controllability in Males But Not in Females

Abstract: Background-Numerous studies have implicated neurogenesis in the hippocampus in animal models of depression, especially those related to controllability and learned helplessness. Here, we tested the hypothesis that uncontrollable, but not controllable stress would reduce cell proliferation in the hippocampus of male and female rats, and would relate to the expression of helplessness behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 47 publications
3
92
0
2
Order By: Relevance
“…In this study, we demonstrate that acute, and chronic, stress suppress hippocampal cell proliferation, consistent with previous reports (12,32,33) and that the antiproliferative effect of stress is blocked by inhibition of IL-1RI. In vitro studies show that suppression of cell proliferation is mediated by direct actions of IL-1␤ on IL-1RI receptors localized on adult hippocampal progenitor cells via a reduction in cell cycling and not increased cell death.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we demonstrate that acute, and chronic, stress suppress hippocampal cell proliferation, consistent with previous reports (12,32,33) and that the antiproliferative effect of stress is blocked by inhibition of IL-1RI. In vitro studies show that suppression of cell proliferation is mediated by direct actions of IL-1␤ on IL-1RI receptors localized on adult hippocampal progenitor cells via a reduction in cell cycling and not increased cell death.…”
Section: Discussionsupporting
confidence: 93%
“…Rats exposed to 30 trials of mild footshock for 7 d showed a decrease in the latency to escape the shock (controllable). In contrast, the yoked littermates who were unable to control the stressor (uncontrollable) did not attempt to escape after the first day of training and performed poorly on a subsequent test (FR2) demonstrating their inability to learn to escape the shock (Shors et al, 2007). These observations suggest that the animals subjected to uncontrollable stress exhibit a form of learned helplessness that is an accepted model of depression.…”
Section: Vgf Is Downregulated In Animal Models Of Depression and Prodmentioning
confidence: 95%
“…Estimates of total numbers of BrdU-labeled cells were made using a modified unbiased stereology protocol (8,11,55,56). This was accomplished by counting the number of BrdU-labeled cells in the SGZ, GCL, and hilus on every twelfth unilateral section throughout the DG (21.88 to 24.52 mm anteroposterior) (57).…”
Section: Methodsmentioning
confidence: 99%